Augustinas Voldemaras: a Sketch of Intellectual Biography and Certain Examples of Interdisciplinary Orientation - Gieda, Aurelijus (Sociologija. Mintis ir veiksmas, 2013)
The article takes a look at one of the most controversial personalities of inter-war Lithuania. Augustinas Voldemaras (1883–1942) was educated in classical philology, had a keen interest in universal history and the history of Lithuania and an additional concern in philosophical and sociological issues. A consistent search for integrated and synthetic knowledge, openness to philosophical questions and his disposition to polylogical cooperation of disciplines are some of the principal moments in his intellectual biography. Therefore, the present study attempts to highlight certain contexts of Voldemaras’ intellectual biography, witnessing the tightly intertwining interdisciplinarity, aspirations of some type. While a student, Voldemaras found himself in the environment where the problems of ancient history were addressed at the European level and where attempts were made to bring the research on the classical era carried out in pre-revolutionary Russia closer to Germany, being the leader in this sphere. The openness to interdisciplinary search, postulates of integrated and synthetic knowledge that manifested over a long-term, not to mention his philosophical quests and attempts in the field of history, brought Voldemaras closer to the prominent European philosophical movement Centre International de Synthèse founded by Henri Berr, linked by special ties with the formation of one of the most outstanding 20th century schools of history The Annales School. Voldemaras belonged to the History Section of Henri Berr’s Centre International de Synthèse, thus finding a niche among the distinguished representatives of social sciences and the humanities of that time. There is no wonder that in this respect, Voldemaras established himself in Lithuanian historiography as one of the pioneer figures attempting to overcome the disciplinary isolation of sciences, their one-sided empiricism or the lack of a broader approach towards history. The attention paid by Voldemaras to the philosophical issues of identification of history as a science, deliberate attribution of an important role to theory in social sciences and the humanities, the highlight of interdisciplinary initiatives in these sciences are what add the aspect of appeal to his intellectual biography. Voldemaras himself becomes one of the most interesting Lithuanian intellectuals of the first half of the 20th century.